Calcium Transient and Sodium-Calcium Exchange Current in Human versus Rabbit Sinoatrial Node Pacemaker Cells - Arie O. Verkerk; Marcel M. G. J. van Borren; Ronald Wilders (The Scientific World Journal)
There is an ongoing debate on the mechanism underlying the pacemaker activity of sinoatrial node (SAN) cells, focusing on the relative importance of the “membrane clock” and the “Ca2+ clock” in the generation of the small net membrane current that depolarizes the cell towards the action potential threshold. Specifically, the debate centers around the question whether the membrane clock-driven hyperpolarization-activated current, If, which is also known as the “funny current” or “pacemaker current,” or the Ca2+ clock-driven sodium-calcium exchange current, INaCa, is the main contributor to diastolic depolarization. In our contribution to this journal’s “Special Issue on Cardiac Electrophysiology,” we present a numerical reconstruction of If and INaCa in isolated rabbit and human SAN pacemaker cells based on experimental data on action potentials, If, and intracellular calcium concentration ([Ca2+]i) that we have acquired from these cells. The human SAN pacemaker cells have a smaller If, a weaker [Ca2+]i transient, and a smaller INaCa than the rabbit cells. However, when compared to the diastolic net membrane current, INaCa is of similar size in human and rabbit SAN pacemaker cells, whereas If is smaller in human than in rabbit cells.